MAKNA RITUAL KEMATIAN DALAM TRADISI ISLAM JAWA - Abdul Karim (Fakultas Ilmu Budaya Universitas Diponegoro, 2017)
Death is an important event that is deeply moving in a drama of life, so that such events never allowed to pass. In the traditiorfoiety, the death is always raising different ritual, that is, the sacred ritual. Javanese moslems have special ritual. The ritual is acculturation between Hindu, Budha and Islamic continually in the past, and now it appears a new tradition. This tradition is different from those in other countries